Designing a Pilot Study Protocol to Test a Male Alcohol Use and Intimate Partner Violence Reduction Intervention in India: Beautiful Home - Hartmann, Miriam A.; Datta, Saugato; Banay, Rachel F.; Caetano, Vivien; Floreak, Rosii; Appaiah, Prarthana; Sreevasthsa, Anuradha; Thomas, Susan; Selvam, Sumithra; Barnette, Quinn; Srinivasan, Krishnamachari (Frontiers in Public Health, 2018)
Introduction: Evidence suggests alcohol consumption is correlated with intimate partner violence (IPV) making alcohol reduction interventions a promising method for reducing IPV. While both financial incentive and cognitive behavioral therapy (CBT) interventions in high-income countries, respectively, have effectively reduced alcohol consumption and IPV perpetration among men, little evidence exists demonstrating that these approaches can work in a low-resource setting. Methods: The objective of this study is to design and pilot test a low-cost, scalable intervention for reducing alcohol consumption and IPV in Bengaluru, India, where alcohol has been shown to be a key driver of high rates of IPV. A pilot randomized controlled trial (RCT) design will be used to examine the feasibility of testing a combined incentive and CBT based intervention among couples to stimulate immediate behavior change and to sustain positive behaviors pertaining to alcohol use and IPV. Sixty couples will be screened and enrolled into one of three study arms: an incentive-only, incentive plus counselling, or a control arm. Extensive procedures have been included to ensure participant safety, including staff training on global safety procedures for violence intervention research, careful messaging of study aims, screening procedures to exclude those at high risk of alcohol withdrawal or severe violence due to the study, and a referral and case management system. Male and female participants will complete surveys at baseline and immediately and 3-months post-intervention. Breathalyzers will be used to capture male participants’ blood alcohol content daily for intervention arm participants and three times a week for control participants. A sub-sample of male and female members of couples will participate in qualitative in-depth interviews to further explore pathways to change. The results from this preliminary study will inform the development of a larger RCT study of male alcohol and IPV reduction.